2023
DOI: 10.11158/saa.28.4.1
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of ticks (Acari: Ixodidae) on monitored free-ranging giant anteaters and on road-killed anteaters and armadillos in the State of Mato Grosso do Sul, Midwestern Brazil

Abstract: N/A

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
0
0
Order By: Relevance
“…Rhipicephalus microplus is strongly associated with cattle (Nava et al, 2017;Martins et al, 2023), and all the records of parasitism on Subulo gouazoubira, Cerdocyon thous, Puma concolor, and Tapirus terrestris described herein have already been reported previously by other authors. Even though horses are the main host of D. nitens, this parasite has been found in a variety of mammals, including wild carnivores (Labruna et al, 2005b;Guglielmone et al, 2014;Nava et al, 2017).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Rhipicephalus microplus is strongly associated with cattle (Nava et al, 2017;Martins et al, 2023), and all the records of parasitism on Subulo gouazoubira, Cerdocyon thous, Puma concolor, and Tapirus terrestris described herein have already been reported previously by other authors. Even though horses are the main host of D. nitens, this parasite has been found in a variety of mammals, including wild carnivores (Labruna et al, 2005b;Guglielmone et al, 2014;Nava et al, 2017).…”
Section: Discussionsupporting
confidence: 83%
“…As for information about tick species, the largest number of ticks comprising the A. cajennense species complex, represented in Brazil by A. cajennense s.s. and A. sculptum (the vector of R. rickettsii, agent of Brazilian Spotted Fever) (Szabó et al, 2013;Nava et al, 2014;Martins et al, 2016) was expected, given the large numbers of tapirs (n=14), capybaras (n=9) and giant anteaters (n=12), usual hosts for adults and immature stages of A. sculptum (Martins et al, 2016(Martins et al, , 2023. Birds have been recorded as hosts of all the stages of A. sculptum in Brazil (Nava et al, 2017), as reported by Luz et al (2016) in the state of Goiás and observed in this study for A. sculptum nymphs and adult ticks infesting C. cristata in the Cerrado biome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation